Information security policy for organizations implementing e-learning systems. - Tandiono, Ricky. (2008)
This thesis try to map the relation between ISO/IEC 17799:2000 as standards in Information security to SS-496, a Singapore standards for e-Learning. The result of the mapping is to suggest a set of guidelines on information security policy and e-Learning standard that organizations in Singapore could conform to when building e-Learning systems.